On numerical modelling of atmospheric gas dispersion using CFD approach - Tran, Le Vu (2019)
Liquefied Natural Gas (LNG) is the fastest-growing gas supply source due to its economic and environmental benefit. However, LNG storage, handling and transportation are exposed to serious risks to the human, equipment and the environment, due to thermal hazards associated with combustion events such as pool fire, vapour cloud fire, explosion or rapid phase transition. Safety assessment and hazards mitigation method should be applied to lower the possibilities of catastrophic disaster relating to the LNG industry. This study is aimed at developing a CFD model of atmospheric gas dispersion and validating its usage for LNG vapour dispersion. Ensuring accurate description of the Atmospheric Boundary Layer (ABL) is an important task for atmospheric gas dispersion simulation. Either the Reynolds Averaged Navier–Stokes (RANS) equations or Large Eddy Simulations (LES) are used for atmospheric turbulence modelling. The RANS turbulence models are adopted in this study since they are still widely used in practical approach to overcome boundary conditions sensitivity and computationally intensive of the LES. Modelling ABL surface layer as horizontally homogeneous turbulent surface layer (HHTSL) is used to develop a solver for ABL simulation using OpenFOAM CFD library. Monin-Obukhov similarity theory, which is well validated for flows in ABL surface layer over homogeneous surface, is used to model the profiles of velocity, turbulent kinetic energy and turbulence dissipation rate at the inlet boundary. Consistency of flow profiles in HHTSL across the computational domain is ensured by deriving a relation between turbulence model constants and implementing of appropriate wall functions. A dispersion model is developed and validated using experimental data from wind tunnel tests of dense gas dispersion and field experiments of LNG vapour dispersion. The developed model takes into account buoyancy, the heat transfer from ground to the vapour cloud, the effect of variable temperature on gas properties and variable turbulent Schmidt number. The model is also implemented using OpenFOAM CFD library. Statistical Performance Measures (SPM) proposed for LNG dispersion model are used to compare results from developed model and commercial specialized gas dispersion code FLACS (FLame ACceleration Simulator). Results have shown the developed model fulfils requirements of all SPMs and outperforms FLACS in all factors. The developed CFD model enables integration of ABL simulation with gas dispersion simulation. Validation results using benchmark data of dense gas dispersion and LNG vapour dispersion promoted the usage of general CFD in solving industrial safety problem, specifically in risk analysis of atmospheric dispersion of dense gas and LNG spill.